Biocompatible Collagen Films as Substrates for Flexible Implantable Electronics. (2nd July 2015) - Moreno, Salvador; Baniasadi, Mahmoud; Mohammed, Shakil; Mejia, Israel; Chen, Yuanning; Quevedo‐Lopez, Manuel Angel; Kumar, Nalin; Dimitrijevich, Slobodan; Minary‐Jolandan, Majid
Abstract : Collagen, which is the most abundant protein in mammals, is demonstrated as a substrate for flexible implantable electronics. Using electron beam deposition, devices are fabricated on transparent collagen type I films. Several applications, including a strain gauge, a wireless antenna, a heater, and a temperature sensor, are demonstrated, showcasing the promising future applications of this substrate for implantable biomedical devices for monitoring of physiological environment.